The Role of the Social Networking Site (Facebook) in the Adjustment of Youth Trends / Community Issues and Problems - الحديثي عبد القادر صالح (ALBAHITH ALALAMI, 2015)
Recent technological developments in the mass media a major paradigm shift in important segments of society, particularly among young people in particular social networking sites including (Facebook) . it was able to link the sprawling parts of the world and paved the way for all the communities of convergence and exchange views, ideas and desires as provided by their ability to communicate through the use of video clips,pictures,share files, chat, communicate and direct interaction between the audience for this the means. Wondered problem Find the role that can be played using the university youth to the social networking site (Facebook ) to modify their attitudes or their interest in Iraqi society issues, With focused research objectives to identify the size of the assistance provided by the social networking of respondents site to modify their ideas to the Iraqi issues as well as stand on the nature of the issues that he discusses them through (Facebook ) , and choose the researcher (100) Single of university students in the Iraqi university colleges (Science Islamic - Arts and law ) from users of the site through the sample psoriasis , The research has come to group results including those related to increased hours of daily exposure to members of the sample reached between 3-5 hours per day , preferably respondents primarily social networking with friends and relatives and to view events in the world and helped to use this medium respondents dramatically to modify their thoughts toward especially with regard to learning new facts Iraqi issues respondents was established and they are unaware they have other ideas about the issues of Iraq .